Administrative state in comparative perspective - Supernat, Jerzy (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
This article offers an analysis of administrative state from comparative perspective as applied in the recent scientific research and literature.
Keywords: comparison; administration; state